Pendekatan Keadilan Restoratif Sebagai Alternatif Penyelesaian Tindak Pidana Korupsi - Zahra, Arsya Yustisia; Triwati, Ani; Aryaputra, Muhammad Iftar; Abraham, Feri (JURNAL USM LAW REVIEW, 2023)
The purpose of this study is to analyze the restorative justice approach as an alternative to solving corruption by returning state financial losses which are efforts to recover from perpetrators of corruption. The restorative justice approach is a popular approach in recent years, it is possible that this approach can be implemented in corruption crimes. This study uses a normative juridical method with descriptive analytical research specifications. The results of this study indicate that the indicator of restorative justice here is the return of state financial losses. Meanwhile, Article 4 of the PTPK Law regulates the recovery of these losses does not eliminate the punishment of perpetrators of corruption which can be interpreted that Article 4 does not provide loopholes in the application of restorative justice. The application of restorative justice is interpreted not to erase the punishment of the perpetrator but rather to return state finances so that it does not conflict with Article 4, because it will be considered by the judge in imposing a sentence as a mitigating factor. Based on the research results, it is possible to have a restorative justice approach to solve corruption crimes based on SEJA. However, there are several requirements that have been regulated in the SEJA with the criteria of considering small losses, a sense of public awareness that returns state financial losses, and not being continuous. Restorative justice aims at recovering state finances so that the judicial process can stop and can also be followed up. Tujuan dari penelitian ini yaitu untuk menganalisis pendekatan keadilan restoratif sebagai alternatif penyelesaian tindak pidana korupsi dengan mengembalikan kerugian keuangan negara yang merupakan upaya pemulihan dari pelaku tindak pidana korupsi. Penelitian ini menggunakan metode yuridis normatif dengan spesifikasi penelitian deskriptif analitis. Hasil penelitian ini menunjukkan bahwa indikator adanya keadilan restoratif disini adalah pengembalian kerugian keuangan negara. Sedangkan, Pasal 4 UU PTPK mengatur pengembalian kerugian tersebut tidak menghapuskan dipidananya pelaku tindak pidana korupsi yang dapat diartikan bahwa Pasal 4 tidak memberikan celah dalam penerapan keadilan restoratif. Penerapan keadilan restoratif dimaknai tidak menghapus dipidananya pelaku tetapi lebih kepada pengembalian keuangan negara sehingga tidak bertentangan dengan Pasal 4, karena akan menjadi pertimbangan hakim dalam penjatuhan hukuman sebagai faktor yang meringankan. Berdasarkan hasil penelitian dimungkinkan adanya pendekatan keadilan restoratif untuk menyelesaiakan tindak pidana korupsi yang didasarkan pada SEJA. Namun terdapat beberapa persyaratan yang telah diatur dalam SEJA tersebut dengan kriteria yaitu mempertimbangkan kerugian kecil, adanya rasa kesadaran masyarakat yang mengembalikan kerugian keuangan negara, dan tidak bersifat terus menerus. Keadilan restoratif bertujuan sebagai pemulihan keuangan negara sehingga proses peradilan dapat berhenti dan dapat pula ditindaklanjuti.